Recombinant antibodies against Iranian cobra venom as a new emerging therapy by phage display technology - Nazari,Ali (2020)
Abstract Background: The production of antivenom from immunized animals is an established treatment for snakebites; however, antibody phage display technology may have the capacity to delivery results more quickly and with a better match to local need. Naja oxiana, the Iranian cobra, is a medically important species, responsible for a significant number of deaths annually. This study was designed as proof of principle to determine whether recombinant antibodies with the capacity to neutralize cobra venom could be isolated by phage display. Methods: Toxic fractions from cobra venom were prepared by chromatography and used as targets in phage display to isolate recombinant antibodies from a human scFv library. Candidate antibodies were expressed in E. coli HB2151 and purified by IMAC chromatography. The selected clones were analyzed in in vivo and in vitro experiments. Results: Venom toxicity was contained in two fractions. Around a hundred phage clones were isolated against each fraction, those showing the best promise were G12F3 and G1F4. While all chosen clones showed low but detectable neutralizing effect against Naja oxiana venom, clone G12F3 could inhibit PLA2 activity. Conclusion: Therefore, phage display is believed to have a good potential as an approach to the development of snake antivenom.